2022
DOI: 10.1371/journal.pone.0275900
|View full text |Cite
|
Sign up to set email alerts
|

Motives for competitive sports participation in masters track and field athletes: Impact of sociodemographic factors and competitive background

Abstract: Objectives Masters athletes due to their lifelong engagement in sport represent a unique group to study motivation for regular physical activity, but there is less scientific data on the sport motives in masters athletes. Therefore, the aim of this study was to evaluate the association of age, sex, education, nationality, competitive background and training amount with sport motives of masters track and field athletes. Methods 811 (254 women) athletes aged 35–89 years participated in European Veterans Athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…However, some of the findings of the present study differ from those of other works, especially when Masters from other sports are analysed. In contrast to these previous studies, we found no age-or gender-related differences [21,41]. In other studies, men have presented higher achievement goals than women, while the latter showed higher intrinsic motivation scores.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, some of the findings of the present study differ from those of other works, especially when Masters from other sports are analysed. In contrast to these previous studies, we found no age-or gender-related differences [21,41]. In other studies, men have presented higher achievement goals than women, while the latter showed higher intrinsic motivation scores.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, the nature of the rewards in this type of activity is largely symbolic, with there being no significant financial rewards. Additionally, such rewards tend not to be valued by Masters athletes [41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations